Proceedings of FabLearn 2019 2019
DOI: 10.1145/3311890.3311910
|View full text |Cite
|
Sign up to set email alerts
|

"Making" Science Relevant for the 21st Century

Abstract: The Maker Partnership Program (MPP) is an NSF-supported project that addresses the critical need for models of professional development (PD) and support that help elementary-level science teachers integrate computer science and computational thinking (CS and CT 1) into their classroom practices. The MPP aims to foster integration of these disciplines through maker pedagogy and curriculum. The MPP was designed as a research-practice partnership that allows researchers and practitioners to collaborate and iterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In eight studies in our review, teachers reflected on how implementing computing‐integrated lessons supported students in agentive decision making for their own learning, such as positioning students with greater independence. For example, Fancsali et al (2019) reported on a research‐practice partnership with elementary inservice teachers in which professional development and CT‐integrated curricula were iteratively designed. This intensive program involved in‐person professional development, online professional learning communities, and in‐person and virtual coaching.…”
Section: Findings and Analysismentioning
confidence: 99%
“…In eight studies in our review, teachers reflected on how implementing computing‐integrated lessons supported students in agentive decision making for their own learning, such as positioning students with greater independence. For example, Fancsali et al (2019) reported on a research‐practice partnership with elementary inservice teachers in which professional development and CT‐integrated curricula were iteratively designed. This intensive program involved in‐person professional development, online professional learning communities, and in‐person and virtual coaching.…”
Section: Findings and Analysismentioning
confidence: 99%